2021
DOI: 10.1002/ange.202013302
|View full text |Cite
|
Sign up to set email alerts
|

DNA Triplex and Quadruplex Assembled Nanosensors for Correlating K+ and pH in Lysosomes

Abstract: It remains an unanswered question whether the flux of K + and H + in lysosomes are correlated due to difficulties in simultaneously imaging these two ions.This question is of great value for understanding lysosomal acidification. Herein, we designed DNAq uadruplex and triplex based luminescent nanosensors that can, respectively monitor K + and pH in lysosomal lumen. Eachs ensor contained an upconversion nanoparticle luminophore and ag old nanoparticle quencher, producing green and blue luminescence signals for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 52 publications
(2 citation statements)
references
References 84 publications
0
2
0
Order By: Relevance
“…Recently, upconversion nanoparticles (UCNPs), which can absorb NIR light and convert it into UV and visible emissions, have been employed as a light-transducer for activating photoresponsive systems with NIR light. [20][21][22][23][24][25][26] For example, the integration of UCNPs with functional DNA was designed to achieve NIR light-controlled biosensing and therapeutics. [20][21][22]25] Very recently, Liu and McHugh et al reported the design of UCNPs-mediated, NIR lightcontrolled regulation of ChR2 protein and thus neuronal activity.…”
Section: Dynamic Regulation Of Protein Function Is Not Only Essentialmentioning
confidence: 99%
“…Recently, upconversion nanoparticles (UCNPs), which can absorb NIR light and convert it into UV and visible emissions, have been employed as a light-transducer for activating photoresponsive systems with NIR light. [20][21][22][23][24][25][26] For example, the integration of UCNPs with functional DNA was designed to achieve NIR light-controlled biosensing and therapeutics. [20][21][22]25] Very recently, Liu and McHugh et al reported the design of UCNPs-mediated, NIR lightcontrolled regulation of ChR2 protein and thus neuronal activity.…”
Section: Dynamic Regulation Of Protein Function Is Not Only Essentialmentioning
confidence: 99%
“…[16,17,[21][22][23][24] In particular, UCNPs have been combined with DNA-based components to construct biosensors for the detection and imaging of various analytes. [25][26][27][28][29][30] In these designs, acceptors were carefully selected and modified on the surface of UCNPs (as the donor) for the construction of Förster resonance energy transfer (FRET)-based sensors, in which the target detection is based on the changes in UCL intensity. [25] In this Minireview, we summarize the development of UCL-controlled, DNA-based sensor technologies for spatiotemporally selective molecular imaging (Figure 1).…”
Section: Introductionmentioning
confidence: 99%